3m-10=24m-5

Simple and best practice solution for 3m-10=24m-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3m-10=24m-5 equation:


Simplifying
3m + -10 = 24m + -5

Reorder the terms:
-10 + 3m = 24m + -5

Reorder the terms:
-10 + 3m = -5 + 24m

Solving
-10 + 3m = -5 + 24m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-24m' to each side of the equation.
-10 + 3m + -24m = -5 + 24m + -24m

Combine like terms: 3m + -24m = -21m
-10 + -21m = -5 + 24m + -24m

Combine like terms: 24m + -24m = 0
-10 + -21m = -5 + 0
-10 + -21m = -5

Add '10' to each side of the equation.
-10 + 10 + -21m = -5 + 10

Combine like terms: -10 + 10 = 0
0 + -21m = -5 + 10
-21m = -5 + 10

Combine like terms: -5 + 10 = 5
-21m = 5

Divide each side by '-21'.
m = -0.2380952381

Simplifying
m = -0.2380952381

See similar equations:

| x/18+x/3 | | 8(y+6)+y=4(y+5)+2 | | 1/31/2x/3 | | -4(3x-4)+1=-12x+17 | | 5x+4=12+5x | | 2x-3+4x-8=13 | | 5*29= | | 7x-8y=64 | | 11*15= | | 2(x-4)(x-3)=x-13 | | 9x+6=9(x-3) | | X+4/3=x-8/5 | | X/4-3=-4 | | -8-3+6*2= | | 3z=14-29 | | 3(3m-2)+10=3(m-4)-3 | | 23x-7-14x+4=25x-4-16x+12 | | (5a-2)(7a+3)=0 | | 0.14(y-6)+0.04y=0.08y-0.1 | | 5-5(-5-7/-6)-13 | | -4(4x+1)=-52 | | 6x^2=10x+4 | | 3a-6x+4-12a+3x= | | 3(x+2)=-2(x-8) | | x(1-x)=25(x-1) | | 4-(-2n+3)=44 | | x+x+7=160 | | 12x-5=6x-31 | | x(x+9)=-2(x+9) | | 0.9*x+7.8*y=114 | | -3b+4/3b=-40/9 | | 2a+a+6-13= |

Equations solver categories